Evaluating the impact of innovative cyber technologies on the delivery process of South African sustainable affordable housing - Mahachi, Jeffrey (Department of Construction Economics and Management, 2025)
The present study aimed to evaluate the impact of innovative technologies on the delivery and affordability of low-income housing in South Africa. Given the rising demand for affordable housing due to a growing population and urbanisation, the study aimed to investigate the role of new technologies in enhancing housing delivery. The study explored the use of various innovative technologies such as Unmanned Aerial Vehicles (UAVs), Building Information Modelling (BIM), Geographic Information Systems (GIS), 3D Printing, Virtual Reality (VR), Augmented Reality (AR), Artificial Intelligence (AI), Smart Sensors, Modular and Prefabrication, Object-Oriented Programming (OOP), and Project Portfolio Management (PPM) as potential solutions. The research adopted a mixed-method approach, combining qualitative and quantitative methods. The target population included home developers, experts, policymakers, and academics involved in affordable housing development. Qualitative data were gathered through expert interviews until saturation was achieved, while quantitative data was obtained from 100 survey questions filled out by experts involved with affordable housing in South Africa. The data analysis method consisted of thematic analysis and descriptive and inferential statistics. The results of the study indicated that these innovative technologies have the potential to not only accelerate the delivery of affordable housing but also make it more cost-efficient. The analysis showed that 3D printing, modular and prefabrication were three technologies that could significantly increase housing delivery, while BIM, GIS, VR, OOP, and PPM could efficiently aid in the planning of affordable housing, reducing design conflicts, improving project schedules, and cutting development costs. Smart Sensors, AR, and UAVs could indirectly enhance housing delivery by monitoring construction, ensuring the site is built on schedule and correctly, and monitoring construction worker productivity. However, the study also identified high costs and limited social acceptance as major challenges. To address these issues, the study emphasised the need for the government to promote the adoption and implementation of these technologies through financial incentives and subsidies for companies that adopt them, as well as investment in research and development. The study also stressed the importance of promoting the use of these technologies in high-end housing developments in addition to affordable housing projects. In conclusion, the results of this study highlight the significance of considering innovative technologies in the delivery of affordable housing in South Africa. The findings suggest that the government has a critical role to play in promoting the adoption and implementation of these technologies through financial incentives and investment in research and development, helping to overcome current challenges and making affordable housing a reality for all.